Developing Life Skills Through Physical Education: Social Skills and Teamwork in Moroccan Secondary School Students - Abdelmajid Ouaddou; Abdelkrim Kanbaai (Central European Journal of Sport Sciences and Medicine, 2025)
Life skills are a combination of psychosocial and interpersonal skills that can have an impact on physical, mental and social well-being. Social skills include the ability to make judgments and act in different social situations. Physical education (PE) can play an important role in developing life skills in Moroccan secondary school students. This cross-sectional study aims to examine the impact of handball on the development of social and teamwork skills in 150 Moroccan secondary school students, and to explore the relationship between social skills and teamwork. In our research, we used two different methods to gain an in-depth understanding of students' views on how they perceived the development of their social and teamwork skills. To do this, we conducted mixed-method research using both the Sports Life Skills Scale (LSSS) and participant observation on a sample of 150 schoolchildren, including 76 boys and 74 girls aged between 14 and 20, in the rural BITT commune of El Hajeb (Morocco), during a 12-session handball learning cycle during the school season (2022/2023). Data analysis was performed using multivariate analysis of variance, Pearson correlation and multiple regressions. The results showed that BITIT secondary school students felt they were developing their teamwork skills with (WM=3.62, SD=0.662) and their social skills with (WM=3.54, SD=0.740) through playing handball. There was a significant correlation (r=0.429; p0.01) between social skills and teamwork skills. The results of this study suggest that team sports can be an excellent medium for the development of social skills and teamwork in students. In this way, students not only improve their physical health, but also acquire essential skills that will be useful in all areas of their lives.